2017
DOI: 10.1016/j.rmed.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Parametric response mapping on chest computed tomography associates with clinical and functional parameters in chronic obstructive pulmonary disease

Abstract: Background In the search for specific phenotypes of chronic obstructive pulmonary disease (COPD) computed tomography (CT) derived Parametric Response Mapping (PRM) has been introduced. This study evaluates the association between PRM and currently available biomarkers of disease severity in COPD. Methods Smokers with and without COPD were characterized based on questionnaires, pulmonary function tests, body plethysmography, and low-dose chest CT scanning. PRM was used to calculate the amount of emphysema (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 24 publications
0
58
0
Order By: Relevance
“…As a result, functional small airways disease appears to be the major contributor of FEV1 decline in COPD patients. Another recent study found a strong correlation between PRM and COPD disease and severity [34]. Consistently, the functional small airway disease component correlated specifically with increased residual volume and the emphysema component with lowered carbon monoxide diffusion.…”
Section: Imaging Small Airwaysmentioning
confidence: 55%
“…As a result, functional small airways disease appears to be the major contributor of FEV1 decline in COPD patients. Another recent study found a strong correlation between PRM and COPD disease and severity [34]. Consistently, the functional small airway disease component correlated specifically with increased residual volume and the emphysema component with lowered carbon monoxide diffusion.…”
Section: Imaging Small Airwaysmentioning
confidence: 55%
“…Chest computed tomography (CT) offers the possibility of quantifying the amount of emphysema. The number of chest CT acquisitions is expected to increase due to the favourable results of the National Lung Screening Trial [ 1 ] and the interest in subtyping chronic obstructive pulmonary disease (COPD) patients [ 2 ]. Additional quantification of emphysema on screening CT acquisitions will therefore likely gain importance.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple metrics have been proposed to measure small airway disease while minimizing the impact of emphysema (3). Parametric response mapping (PRM) uses image matching to estimate nonemphysematous gas trapping and provides an estimate of functional small airway disease (fSAD) that is associated with lung function and respiratory morbidity parameters, but it is based on determination of emphysema and gas-trapping regions using fixed lung density thresholds (4)(5)(6). Although PRM is a useful tool, the dependence on density thresholds may result in missing detection of mild density abnormalities.…”
mentioning
confidence: 99%